Intercropping pays dividend to farmer - Sharma, Ramakant; Porwal, R (Indian Horticulture, 2020)
Roop Chand Kahar, a farmer of village Nadi ii (Ajmer, Rajasthan) was growing flowers and vegetables with traditional method of agriculture. He was not earning desired profit due to pest problem and higher labour cost. The idea of intercropping of marigold + coriander, marigold + cabbage, marigold + cauliflower, marigold + tomato and marigold + chilly helped him to harness potential yield and achieving more profit as compared to sole crop.